Team Goal Clarity and Individual Adaptive Performance of SME Employees: A Sequential Mediated Multilevel Model - Muhammad Shahid; Farhan Sarwar; Shoaib Aslam; Muhammad Bilal (SAGE Open)
Adaptive performance of employees is a crucial determinant of successful change, fostering innovation and resilience in the dynamic business environment. This research presents a multilevel framework which explores the sequential mediating role of team learning orientation and individual entrepreneurial orientation in the impact of team goal clarity on employee’s adaptive performance. Conducted in the scenario of small and medium enterprises (SMEs) in Pakistan, the study employees a time-lagged survey design to gather data. Mplus was used for multilevel modelling in which team goal clarity and team learning orientation were group level variables and entrepreneurial orientation and adaptive performance were individual level. The results highlighted that team learning orientation plays a pivotal role in enhancing the entrepreneurial orientation of individual employees, subsequently enhancing adaptive performance. The research responds to various calls in existing literature to investigate the group level antecedents and underlying multilevel mechanism leading to adaptive performance. The study contributes to the broader perspective in understanding team dynamics, learning orientations, and entrepreneurial behaviors within SMEs.